Intervenção arqueológica no Alto do Calvário, Miranda do Corvo: a necrópole rupestre - Vera Santos (Medievalista)
It is probable that the town of Miranda do Corvo has developed around the mound of the old castle, an important fortification in the defense of Coimbra during the 'Reconquista'. However, nothing is known about its history. It is almost certain that the toponym Miranda has Latin origin, related to the function of the hill as a lookout. However, the first documentary reference to this village appears in the tenth century, and its castle appears only mentioned after the twelfth century. Today, however, virtually nothing remains of medieval fortification, except a tower – current bell tower of the church – that would be part of the wall, as well as the cistern, located at the top of the hill.The archaeological work here presented, performed at the request of the Municipality, takes place under the project Rede Urbana dos Castelos e Muralhas Medievais do Mondego, in order to carry out a rehabilitation program.